2022
DOI: 10.1038/s41467-022-34421-3
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic charge trapping in phototransistors unlocks ultrasensitive polarimetry for bionic navigation

Abstract: Being able to probe the polarization states of light is crucial for applications from medical diagnostics and intelligent recognition to information encryption and bio-inspired navigation. Current state-of-the-art polarimeters based on anisotropic semiconductors enable direct linear dichroism photodetection without the need for bulky and complex external optics. However, their polarization sensitivity is restricted by the inherent optical anisotropy, leading to low dichroic ratios of typically smaller than ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…[3][4][5]41] According to Fresnel's law, when sunlight illuminates the surface of an obvious, most of the scattered or reflected light from the surface is partially polarized, which is the most ubiquitous and fundamental phenomenon in nature. [7,42] The polarized light is not perceptible for humans, but it could be well detected by many insects. As shown in Figure 5a, the visual system of honeybees is exquisitely sensitive to the polarized light, which is only mediated by a special group of ommatidia located in the dorsal rim area (DRA) of compound eye.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5]41] According to Fresnel's law, when sunlight illuminates the surface of an obvious, most of the scattered or reflected light from the surface is partially polarized, which is the most ubiquitous and fundamental phenomenon in nature. [7,42] The polarized light is not perceptible for humans, but it could be well detected by many insects. As shown in Figure 5a, the visual system of honeybees is exquisitely sensitive to the polarized light, which is only mediated by a special group of ommatidia located in the dorsal rim area (DRA) of compound eye.…”
Section: Resultsmentioning
confidence: 99%
“…[368] Photodetectors having light polarization sensitivity besides selfpowered nature will play a major role in the future development of miniaturized sensors for applications such as intelligent recognition, bionic navigation, and so on. [48,369] Recently, Quan et al [235] reported on the self-powered operation of p-GaSe/n-ReS 2 polarization-sensitive photodetector. Multilayer GaSe (p-type) with a band gap of ≈2.05 eV can form a type II heterojunction with few-layer ReS 2 (n-type).…”
Section: Heterojunction-based Polarization Sensitive Photodetectorsmentioning
confidence: 99%
“…Given the needs of IoT application and low power dissipation, self-powered photodetectors that convert light into electric signals in the absence of external bias have ushered in research and development boom in a variety of fields like thermal imaging, surveillance, optical communication, environmental monitoring, and so forth. Especially, 2D vdW heterostructures driven by the built-in electric field provide a degree of freedom for self-powered photodetection with on-chip integration technology, which benefit from adjustable atomic thicknesses, negligible lattice mismatching constraints, the strong layer-by-layer coupling effect, etc. A wealth of all-2D vdW SHJ devices fabricated by the artificial stacking or vdW epitaxy techniques have been reported to realize self-powered photodetection. For example, Xin et al reported an artificial stacked GeSe/MoS 2 vdW heterojunction photodetector with a moderate EQE of 24.2% .…”
Section: Introductionmentioning
confidence: 99%